1819 & Before : Singapore's Pasts - Guan, Kwa Chong (Book collections on Project MUSE., 2021)
The essays published here began as a series of lectures commemorating the bicentennial of Thomas Stamford Raffles's establishment of a British Station in 1819. The essays draw on thirty-five years of archaeological investigations on and around Fort Canning, new readings of the Malay Annals, early Chinese records reporting Singapore, and the Portuguese and Dutch records to probe and challenge our understanding of Singapore's history before Raffles. Altogether, these essays suggest that Singapore had a pre-1819 past that was deeply connected to the millennium-long maritime history of the Straits.